High-solid-content waterborne polyurethane as well as internal-external emulsification preparation method and application thereof
Through the internal-external emulsification bonding method and the optimization of external emulsifier, the problems of high viscosity, unstable emulsion and difficult to advance the phase transition point during the preparation of high-solid content water-based polyurethane are solved, and the solid content and performance optimization of WPU are achieved.
Patent Information
- Application Number
- CN202510290586.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-12
AI Technical Summary
The existing high-solid content water-based polyurethane (WPU) has problems such as high viscosity, unstable emulsion and difficult to advance the phase transition point during the preparation process, resulting in a solid content below 40%.
The internal-external emulsification combination method is adopted to introduce external emulsifiers to optimize the type and dosage of external emulsifiers. Through the combined use of carboxylic acid/sulfonic acid type WPU, the solid content and stability of WPU are significantly improved.
The solid content of WPU has been increased to about 50%, and a smaller particle size, higher stability, better water resistance and mechanical properties have been achieved.
Smart Images

Figure CN119798605A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane, and in particular relates to a high-solid content waterborne polyurethane and an internal-external emulsification preparation method and application thereof. Background Art
[0002] High-solid content waterborne polyurethane (WPU) has obvious advantages over low-solid content WPU due to its fast film-forming and drying speed, low energy consumption, high equipment utilization, and low transportation cost. However, there are many technical difficulties in its preparation process, among which the most prominent are reducing the viscosity of the system, maintaining the stability of the emulsion, and controlling the phase inversion point. The compound use of carboxylic acid / sulfonate gives the WPU emulsion good stability. At the same time, by adjusting the raw material ratio, R value, and the dosage and compound ratio of sulfonic acid / carboxylic acid hydrophilic chain extender, the viscosity of the prepolymer is reduced, creating good conditions for the preparation of high-solid content WPU. However, due to the limited content of hydrophilic groups in the prepolymer, the phase inversion point cannot be significantly advanced, so the solid content of the prepared WPU is less than 40%.
[0003] External emulsifiers are amphiphilic molecules that contain both hydrophilic and lipophilic groups. During emulsification, external emulsifiers can form micelles at the oil-water interface, with their hydrophilic ends extending into the water, wrapping the latex particles inside, thereby stably suspending them in the water. At the same time, the use of external emulsifiers can reduce the surface tension of the dispersed phase, forming a thin film or double electrical layer on the surface of the dispersed phase droplets to prevent the droplets from aggregating and condensing with each other, thereby improving the stability of the emulsion.
[0004] CN117003986A discloses an aqueous polyurethane dispersion, the raw materials for its preparation include a combination of a prepolymer, a chain extender and an external emulsifier, the raw materials for the preparation of the prepolymer include, by weight: 7-15 parts of isocyanate, 25-43 parts of polyol, 0.2-2 parts of reactive internal emulsifier, the isocyanate includes 1,5-pentamethylene diisocyanate; the mass percentage of 1,5-pentamethylene diisocyanate in the isocyanate is ≥30%, and the external emulsifier includes any one of anionic surfactants, cationic surfactants, nonionic surfactants, polyvinyl alcohol or water-soluble cellulose or a combination of at least two. This method studies the influence of the PDI content and NCO / OH ratio in the isocyanate component of the prepolymer on the viscosity, particle size and solid content of the emulsion, but it does not involve the influence of the type of external emulsifier on the performance of WPU. Summary of the invention
[0005] The present invention introduces an external emulsifier, utilizes an internal-external emulsification combination method to prepare a solvent-free carboxylic acid / sulfonic acid type WPU, optimizes the type and amount of the external emulsifier, thereby increasing the solid content of the waterborne polyurethane and giving the WPU a smaller particle size, higher stability, and better water resistance and mechanical properties.
[0006] The present invention first provides an internal-external emulsification preparation method of high-solid content waterborne polyurethane, which comprises the following steps: The polyether polyol, isocyanate and chain extender are mixed, and then a catalyst is added, and after the temperature is raised for reaction, the temperature is lowered, and then a neutralizer is added. After the neutralization reaction, an external emulsifier is added to the system, and after the external emulsification reaction, a waterborne polyurethane is obtained; Wherein, the ratio of the molar amount of the isocyanate to the total molar amount of the polyether polyol and the chain extender is 1 to 3; The chain extender is a combination of chain extender A and chain extender B; The chain extender A is at least one of DMPA (2,2-dihydroxymethyl propionic acid) or DMBA (2,2-dihydroxymethyl butyric acid); The chain extender B is at least one of BES-Na (sodium N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonate) or AAS-Na (sodium 2-[(2-aminoethyl)amino]ethanesulfonate); The amount of chain extender B added accounts for 1-20% of the total mass of chain extender A and chain extender B; The amount of the chain extender added is 1% to 5% of the total mass of the polyether polyol, isocyanate and chain extender; The external emulsifier is an anionic external emulsifier; The amount of the external emulsifier added is 0.1% to 2.0% of the total mass of the polyether polyol, isocyanate and chain extender.
[0007] Preferably, in the above preparation method, the chain extender is a combination of DMPA and BES-Na, and the added amount of BES-Na accounts for 5-10% of the total mass of DMPA and BES-Na.
[0008] Preferably, in the above preparation method, the amount of the chain extender added accounts for 3% to 4% of the total mass of the polyether polyol, isocyanate and chain extender.
[0009] Preferably, in the above preparation method, the external emulsifier is SDS (sodium dodecyl sulfate) or LAS (sodium dodecylbenzene sulfonate).
[0010] Preferably, in the above preparation method, the amount of the external emulsifier added is 1% to 1.5% of the total mass of the polyether polyol, isocyanate and chain extender.
[0011] More preferably, in the above preparation method, the added amount of the external emulsifier is 1.5% of the total mass of the polyether polyol, isocyanate and chain extender.
[0012] Preferably, in the above preparation method, the external emulsifier is added dropwise into the system in the form of an aqueous solution of the external emulsifier, and the mass concentration of the aqueous solution of the external emulsifier is 10-20 g / L.
[0013] Wherein, in the above preparation method, the polyether polyol is at least one of polyester polyol, polycaprolactone polyol, polycarbonate polyol, polyethylene oxide polyol, polypropylene oxide polyol, ethylene oxide-propylene oxide copolymer polyol, polytetramethylene glycol polyol, polypropylene glycol ether polyol, vegetable oil polyol, polyesteramide polyol, polythioether polyol, polyacetal polyol, polyolefin polyol or polysiloxane polyol.
[0014] Preferably, in the above preparation method, the polyether polyol is polyether N210.
[0015] Wherein, in the above preparation method, the number average molecular weight of the polyether polyol is 300-5000.
[0016] Preferably, in the above preparation method, the number average molecular weight of the polyether polyol is 500-1500.
[0017] Wherein, in the above preparation method, the isocyanate is at least one of IPDI (isophorone diisocyanate), MDI (diphenylmethane diisocyanate), HDI (hexamethylene diisocyanate), TDI (toluene diisocyanate) or HMDI (dicyclohexylmethane diisocyanate).
[0018] Preferably, in the above preparation method, the isocyanate is IPDI (isophorone diisocyanate).
[0019] Preferably, in the above preparation method, the ratio of the molar amount of the isocyanate to the total molar amount of the polyether polyol and the chain extender is 1.3 to 1.7.
[0020] More preferably, in the above preparation method, the ratio of the molar amount of the isocyanate to the total molar amount of the polyether polyol and the chain extender is 1.5.
[0021] In the above preparation method, the catalyst can be a common catalyst used in the synthesis of waterborne polyurethane in the art, such as dibutyltin dilaurate or an organic bismuth catalyst Valikat Bi2010, etc.; the amount of the catalyst added is generally a catalytic amount added dropwise to the system, specifically, the amount of the catalyst added is generally 1-10% of the molar amount of the polyether polyol.
[0022] Wherein, in the above preparation method, the neutralizing agent is at least one of alkali metal hydroxide, alkali metal carbonate, 2-amino-2-methyl-1-propanol, methyldiethanolamine, dimethylethanolamine, diethylethanolamine, triisopropanolamine, ammonia water or triethylamine.
[0023] Preferably, in the above preparation method, the neutralizing agent is NaOH, KOH, ammonia water or triethylamine.
[0024] Wherein, in the above preparation method, the molar ratio of the neutralizing agent to the molar ratio of the chain extender is 0.9 to 1.1.
[0025] Preferably, in the above preparation method, the molar ratio of the neutralizer to the molar ratio of the chain extender is 0.99 to 1.01.
[0026] Wherein, in the above preparation method, the temperature of the temperature-raising reaction is 60~100°C.
[0027] Wherein, in the above preparation method, the time of the temperature rising reaction is 2 to 6 hours.
[0028] Wherein, in the above preparation method, the cooling is to below 30°C.
[0029] Wherein, in the above preparation method, the neutralization reaction time is 10 to 60 minutes.
[0030] Wherein, in the above preparation method, the stirring speed of the external emulsification reaction is 200~800rpm.
[0031] Wherein, in the above preparation method, the time of the external emulsification reaction is 0.5~2h.
[0032] The present invention also provides a high-solid content waterborne polyurethane, which is prepared by the above preparation method, and the solid content of the waterborne polyurethane is not less than 48%. The waterborne polyurethane has excellent stability, and its storage stability is greater than 6 months, and it can be diluted with water in any proportion without precipitation.
[0033] The high-solid content waterborne polyurethane provided by the present invention has excellent properties, so the present invention also provides the use of the waterborne polyurethane in inks, coatings, adhesives or textiles.
[0034] Beneficial effects of the present invention: The present invention adopts a method of combining internal and external emulsification, takes carboxylic acid and sulfonate compounds as chain extenders, explores the emulsification effect of nonionic and anionic external emulsifiers, and the influence of the amount of external emulsifier on the performance of WPU, and prepares a WPU emulsion with a solid content of about 50%. Under solvent-free conditions, the present invention introduces sulfonic acid and carboxylic acid simultaneously in the molecular structure of WPU, and combines anionic external emulsifiers to significantly improve the solid content and stability of WPU, improve the comprehensive properties of WPU such as water absorption performance and mechanical properties, and the obtained high-solid content WPU can be diluted with water at will, and has good application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the reaction formula for preparing WPU in the examples.
[0036] Figure 2 Particle size distribution diagram of WPU emulsion with different LAS contents.
[0037] Figure 3 The infrared analysis spectra of WPU films with LAS contents of 0 and 1.5%.
[0038] Figure 4 This is the test result of water absorption performance of WPU films with different LAS contents.
[0039] Figure 5 This is a graph showing the mechanical properties test results of WPU films with different LAS contents. DETAILED DESCRIPTION
[0040] The present invention is further described in detail below by way of examples, but the protection scope of the present invention is not limited to the scope of the examples.
[0041] The raw materials used in the examples of the present invention are shown in Table 1. All purchased reagents were used directly without secondary purification.
[0042] Table 1 Raw materials required for material preparation
[0043] The analysis and testing method of the embodiment of the present invention is as follows: 1. Fourier transform infrared spectroscopy (FT-IR) test: carried out at room temperature, with a scanning range of 4000cm -1 Up to 400cm -1 .
[0044] 2. Emulsion appearance: Observe the sample's color, state, uniformity and other physical forms with the naked eye. Observe the color of the WPU emulsion to see if there is yellowing, gelation, stratification and other phenomena.
[0045] 3. Mechanical stability: Add the prepared WPU emulsion of equal mass into the same centrifuge tube, put it into the centrifuge, and centrifuge it at 3000r / min for 15min. If the emulsion does not stratify and precipitate, it proves that the emulsion can be stably stored for more than 6 months.
[0046] 4. Storage stability: Leave it at room temperature and observe whether stratification occurs. The stratification time is used as the indicator of stability determination.
[0047] 5. Determination of solid content: The solid content is tested in accordance with GB1725-2007. Weigh 1-2g of WPU emulsion sample and put it into a dry weighing bottle. Then place it in a constant temperature oven at (105+2)℃ and dry until constant weight is reached (the difference between the two weighings is no more than 0.001g, and the minimum value is taken). The solid content of the emulsion is calculated as shown in formula (1), which is: X=(W1-W0) / W×100%.
[0048] In formula (1): X is the solid content of the sample, %; W1 is the total mass of the dried sample and the weighing bottle, g; W0 is the mass of the weighing bottle, g; W is the mass of the sample, g.
[0049] 6. Water absorption test: Take the dried WPU film, weigh it to get m0, and put it into deionized water. After leaving it at room temperature for 24 hours, take it out, use filter paper to fully absorb the residual water on the surface, weigh it to get m1, and perform three parallel experiments. According to formula (2), the water absorption rate of WPU can be calculated. Formula (2) is: Water absorption rate = (m1-m0) / m0×100%.
[0050] In formula (2): m0 is the mass of dry WPU film, g; m1 is the mass of WPU film after water absorption, g.
[0051] 7. Particle size test: The particle size of the emulsion is measured using Zeta potential and nanoforce analyzer.
[0052] 8. Differential Scanning Calorimetry (DSC): Conducted in N2 atmosphere, sample mass 6~10 mg, temperature range -50~150℃, heating and cooling rate 10℃ / min.
[0053] 9. Thermogravimetric analysis test (TGA): carried out in N2 atmosphere, with a heating rate of 20℃ / min, a temperature range of 30-700℃, and a sample weight range of 3-10mg.
[0054] 10. Mechanical properties test: According to GB / T 1040.1-2018 standard, the mechanical properties were tested using a microcomputer-controlled electronic universal testing machine with a tensile rate of 50 mm / min. The results were repeated 5 times and the average value was taken.
[0055] 11. Pencil hardness: Test the pencil hardness of WPU coating according to the method of GB / T6739-1996, the test range is: 6H~6B. Place the coating sample horizontally and fix it. Fix the pencil on the trolley at 45° to the coating surface, push the trolley to make the pencil leave scratches on the coating surface, clean it with a soft brush and observe the degree of damage to the coating surface.
[0056] 12. Adhesion: Test the coating adhesion level according to the method of GB / T9286-1998. Use a grid knife to draw a grid on the coating at a spacing of 1 mm. Then, use 3M tape to stick it tightly on the surface of the coating, and then tear off the tape at a steady speed. By observing the number of grids peeled off on the paint film, the adhesion level of the paint film can be evaluated. The adhesion level is divided into six levels, namely 0, 1, 2, 3, 4, and 5, among which level 0 represents the best adhesion. The judgment criteria are shown in Table 2.
[0057] Table 2 Adhesion test results classification
[0058] 13. Contact angle test (CA): Use a contact angle tester to test the hydrophobicity of the WPU film surface. Take the average value after five tests.
[0059] Experimental methods of the embodiments of the present invention: 1. Preparation of WPU emulsion by internal-external emulsification combination method: The synthesis process is as follows Figure 1 As shown. The polyether N210 is heated and decompressed for dehydration and then used. According to Table 3, the measured polyether N210, IPDI, DMPA and BES-Na are added to a three-necked flask, and dibutyltin dilaurate is added dropwise at one time, and the reaction is carried out at 80°C for 4 hours. After the reaction is completed, the temperature is lowered to below 30°C, and the measured TEA is added and reacted for 30 minutes. After the neutralization is completed, the external emulsifier (fatty alcohol polyoxyethylene ether, polyethylene glycol dioleate, SDS or LAS, mass concentration 15g / L) dissolved in water is slowly and uniformly added within 5 minutes, and sheared for 1 hour under high-speed stirring to obtain WPU emulsion.
[0060] Table 3 Formulations of WPU with different R values
[0061] In Table 3, the calculation method of raw material dosage is as follows: (1) First, specify the R value, determine the amount of polyether N210, DMPA, and BES-Na, and use the R value to calculate the amount of IPDI to ensure W 扩链剂 % = 2% ~ 5%; R = -NCO / -OH, that is, the ratio of the molar amount of IPDI to the total molar amount of polyether N210, DMPA and BES-Na, W扩链剂 % =(m DMPA + m BES-Na ) / m 预聚物 , m 预聚物 = m 聚醚N210 + m IPDI + m DMPA + m BES-Na , m represents mass, unit is g.
[0062] (2) The amount of dibutyltin dilaurate used each time is about 0.3g. Dibutyltin dilaurate is a catalyst. It is sufficient to ensure that the amount used each time is basically the same.
[0063] (3) TEA is a neutralizing agent, and its molar number is consistent with the total molar number of DMPA and BES-Na.
[0064] (4) Amount of external emulsifier added W 外乳化剂 %=0, 0.5%, 1.0%, 1.5% or 2.0%, W 外乳化剂 % =m 外乳化剂 / m 预聚物 .
[0065] 2. Preparation of WPU film: The emulsion was evenly poured into a 1 cm×8 cm polytetrafluoroethylene plate at room temperature, dried at room temperature for 48 h, and dried in a vacuum oven at 80° C. to obtain a WPU film, which was stored for later use.
[0066] Example 1: Effect of external emulsifier type on WPU emulsion and film properties DMPA and BES-Na were used as chain extenders, R = 1.5, neutralization degree 100%, BES-Na accounted for 6% of the total chain extender, and the total content of chain extender (W 扩链剂 %=m 扩链剂 / m 预聚体 ) is about 3.55%, and fatty alcohol polyoxyethylene ether (AEO-9), polyethylene glycol dioleate (Emerest2648), sodium dodecyl sulfate (SDS), and sodium dodecylbenzene sulfonate (LAS) are selected as external emulsifiers, respectively. The amount of external emulsifier is kept at 1.5% of the total mass of the prepolymer. The influence of the type of external emulsifier on the performance of WPU is shown in Table 4.
[0067] Table 4 Effect of external emulsifier type on WPU properties
[0068] As shown in Table 4, the use of external emulsifier significantly increased the solid content of WPU. The solid content of WPU prepared by the internal-external emulsification method was maintained at about 50%. This is because during emulsification, the lipophilic end segment structure in the external emulsifier can be well soluble in the polymer, and its hydrophilic end can interact with water molecules, which improves the hydrophilicity of the prepolymer and is conducive to the early phase transition point, thereby increasing the solid content of WPU. The appearance of WPU with the addition of anionic external emulsifiers (LAS, SDS) is better than that of WPU with the addition of non-ionic external emulsifiers (AEO-9, Emerest2648). This is because the anionic external emulsifier can be ionized in water and form a stable double layer on the surface of the latex particles. Due to electrostatic repulsion, the latex particles can be more stably suspended in water, which is more conducive to the formation of an emulsion with a smaller particle size. The macroscopic appearance is that the emulsion is milky white with a slight blue glow. The stability of WPU synthesized with Emerest2648 as an external emulsifier is poor, which is due to the small HLB (hydrophile-lipophile balance) value of Emerest2648 [HLB (LAS) = 10.6, HLB (SDS) = 40, HLB (AEO-9) = 12.5, HLB (Emerest2648) = 7.5], the emulsification performance is poor, resulting in poor stability of WPU emulsion.
[0069] Example 2: Effect of external emulsifier content on WPU emulsion and film properties 1. Considering the emulsion performance comprehensively, on the basis of Example 1, LAS was selected as the external emulsifier, and the other conditions were kept unchanged, and only the amount of the external emulsifier (w LAS % = m LAS / m 预聚体 ), the effect of external emulsifier content on the properties of WPU emulsion and film is shown in Table 5.
[0070] Table 5 Effect of external emulsifier content on WPU properties
[0071] As shown in Table 5, with the increase in the amount of external emulsifier, the appearance of the emulsion gradually changes from milky white to milky white with a slight blue glow, the stability gradually increases, and the solid content increases. This is because the content of hydrophilic groups in the WPU prepolymer is relatively small. If no external emulsifier is added, when the solid content is controlled to be above 50%, the prepolymer cannot be successfully emulsified, and flocculation and other phenomena may occur, resulting in poor stability of the emulsion. After adding the external emulsifier, the hydrophilicity of the prepolymer increases and the emulsification performance improves. With the increase in the amount of external emulsifier, the prepolymer is more easily dispersed into latex particles with smaller particle size. The macroscopic manifestation is that the emulsion is slightly blue and the stability is enhanced. It is worth mentioning that when the amount of external emulsifier added reaches more than 1.5%, the solid content of the emulsion tends to be stable. This is because when the amount of external emulsifier increases to a certain value, the critical micelle concentration is reached. After reaching this concentration, the surface tension of the emulsion tends to be stable, basically unchanged, and the emulsification effect gain is not obvious. Therefore, selecting the external emulsifier dosage near the critical micelle concentration can maximize the emulsification effect.
[0072] 2. The particle size of the WPU emulsion synthesized in this example was detected. The effects of different external emulsifier contents on the particle size of the WPU emulsion are shown in Tables 6 and Figure 2 shown.
[0073] Table 6 Average particle size of WPU emulsions with different external emulsifier contents
[0074] From Table 6 and Figure 2 It can be seen that the particle size of the WPU emulsion synthesized in this embodiment is unimodal, and its distribution range gradually narrows with the increase of the external emulsifier content. With the increase of the external emulsifier content, the average particle size of the emulsion decreases from 320.58nm to 148.19nm. This is because the size of the emulsion particles is affected by many factors such as the hydrophilicity of the prepolymer, molecular weight, and shear speed. When other factors are controlled unchanged, the influence of the hydrophilicity of the prepolymer on the particle size is dominant. With the increase of the external emulsifier content, the hydrophilicity of the WPU prepolymer is enhanced, the number of charged ionic groups on the surface of the latex particles increases, and it is easier to be dispersed into smaller latex particles, the emulsion particle size is reduced, and at the same time, the size of the latex particles is more uniform, and the emulsion particle size distribution becomes narrower.
[0075] 3. The synthesized w LAS When % is 0 and 1.5%, the obtained WPU film is subjected to infrared analysis. The results are as follows Figure 3 shown.
[0076] Depend on Figure 3 It can be seen that the characteristic peak positions of WPU prepared by the internal-external emulsification method are basically the same as those of WPU prepared by the internal emulsification method, indicating the successful synthesis of WPU. Compared with the infrared spectrum of WPU without external emulsifier, the infrared spectrum of WPU with external emulsifier has a wavelength of 3326cm -1、1709cm -1 、1094cm -1 、1019cm -1 There is a slight shift and enhancement at the , which is caused by the overlap of the characteristic peaks of LAS. The infrared spectrum of WPU containing external emulsifier does not show new characteristic absorption peaks, indicating that no new chemical bonds are generated between LAS and WPU, only the physical adsorption and embedding effect of the external emulsifier on the latex particles.
[0077] 4. The water absorption performance of the WPU film synthesized in this example was tested. The influence of different external emulsifier contents on the water absorption performance of the WPU film was as follows: Figure 4 shown.
[0078] Depend on Figure 4 It can be seen that with the increase of the content of the external emulsifier, the water absorption rate of each sample shows a trend of first decreasing and then increasing, while the water contact angle shows a trend of first increasing and then decreasing. This is because the external emulsifier is a surfactant. During the process of emulsion drying and film formation, the external emulsifier tends to gather on the surface of the film, preventing water molecules from entering the interior of the film. However, the improvement of the water resistance of the film by the external emulsifier is limited. The external emulsifier LAS used in this embodiment is a sulfonate. Sulfonic acid is an organic medium-strong acid with good ionization performance in aqueous solution and good water solubility. The increase in its dosage will increase the hydrophilicity of the film, resulting in the water absorption rate of the WPU film increasing with the increase of its content, and the water contact angle decreasing.
[0079] 5. The mechanical properties of the WPU film synthesized in this example were tested. The effects of different external emulsifier contents on the mechanical properties of the WPU film were as follows: Figure 5 shown.
[0080] Depend on Figure 5 It can be seen that with the increase in the amount of external emulsifier, the tensile strength of the film decreases slightly, and the elongation at break first increases slightly and then decreases. This is because LAS is added to WPU as an additive to improve the performance of the emulsion, but as its addition amount gradually increases, it may interfere with the interaction between polyurethane segments, reduce the mutual entanglement of molecular segments and the hydrogen bonding between molecules, resulting in a decrease in the mechanical properties of the WPU film. At the same time, if the amount of LAS added is too large, problems such as uneven dispersion may occur, resulting in a small number of defects in the film and a decrease in mechanical properties.
[0081] In summary, the present invention introduces an external emulsifier and uses an internal-external emulsification combination method to prepare solvent-free carboxylic acid / sulfonic acid type WPU, which can significantly increase the solid content of WPU emulsion (from 38% to 50%); the emulsification effect of anionic external emulsifiers is significantly better than that of non-ionic external emulsifiers, among which the solid content of WPU prepared with LAS as an external emulsifier is slightly higher than that of WPU prepared with SDS as an external emulsifier; the use of external emulsifiers gives WPU emulsions smaller particle size and higher stability, but the increase in its dosage is not conducive to the improvement of water resistance and mechanical properties of the film. When LAS is used as an external emulsifier and the dosage is 1.5%, the solid content of WPU emulsion reaches 51.41%, the average particle size of WPU emulsion is 189.15nm, the tensile strength of WPU film is 1.6Mpa, the elongation at break is 610.7%, the hardness reaches 5H, the adhesion grade is 0, and the comprehensive performance is the best.
Claims
1. An internal-external emulsification method for preparing high solid content waterborne polyurethane, characterized in that: The following steps are involved: The polyether polyol, isocyanate and chain extender are mixed, and then a catalyst is added, and after the temperature is raised for reaction, the temperature is lowered, and then a neutralizer is added. After the neutralization reaction, an external emulsifier is added to the system, and after the external emulsification reaction, a waterborne polyurethane is obtained; Wherein, the ratio of the molar amount of the isocyanate to the total molar amount of the polyether polyol and the chain extender is 1 to 3; The chain extender is a combination of chain extender A and chain extender B; The chain extender A is at least one of DMPA or DMBA; The chain extender B is at least one of BES-Na or AAS-Na; The amount of chain extender B added accounts for 1-20% of the total mass of chain extender A and chain extender B; The amount of the chain extender added is 1% to 5% of the total mass of the polyether polyol, isocyanate and chain extender; The external emulsifier is an anionic external emulsifier; The amount of the external emulsifier added is 0.1% to 2.0% of the total mass of the polyether polyol, isocyanate and chain extender.
2. The method for preparing high solid content waterborne polyurethane by internal-external emulsification according to claim 1, characterized in that: At least one of the following is met: The chain extender is a combination of DMPA and BES-Na, and the amount of BES-Na added accounts for 5-10% of the total mass of DMPA and BES-Na; The added amount of the chain extender accounts for 3% to 4% of the total mass of the polyether polyol, isocyanate and the chain extender.
3. The method for preparing high solid content waterborne polyurethane by internal-external emulsification according to claim 1, characterized in that: At least one of the following is met: The external emulsifier is SDS or LAS; The amount of the external emulsifier added is 1% to 1.5% of the total mass of the polyether polyol, isocyanate and chain extender.
4. The method for preparing high solid content waterborne polyurethane by internal-external emulsification according to claim 1, characterized in that: The external emulsifier is added dropwise into the system in the form of an aqueous solution of the external emulsifier, and the mass concentration of the aqueous solution of the external emulsifier is 10-20 g / L.
5. The method for preparing high solid content waterborne polyurethane by internal-external emulsification according to claim 1, characterized in that: At least one of the following is met: The polyether polyol is at least one of polyester polyol, polycaprolactone polyol, polycarbonate polyol, polyethylene oxide polyol, polypropylene oxide polyol, ethylene oxide-propylene oxide copolymer polyol, polytetramethylene glycol polyol, polypropylene glycol ether polyol, vegetable oil polyol, polyesteramide polyol, polythioether polyol, polyacetal polyol, polyolefin polyol or polysiloxane polyol; The number average molecular weight of the polyether polyol is 300-5000.
6. The method for preparing high solid content waterborne polyurethane by internal-external emulsification according to claim 1, characterized in that: At least one of the following is met: The isocyanate is at least one of IPDI, MDI, HDI, TDI or HMDI; The ratio of the molar amount of the isocyanate to the total molar amount of the polyether polyol and the chain extender is 1.3 to 1.
7.
7. The method for preparing high solid content waterborne polyurethane by internal-external emulsification according to claim 1, characterized in that: At least one of the following is met: The catalyst is dibutyltin dilaurate; The neutralizing agent is at least one of alkali metal hydroxide, alkali metal carbonate, 2-amino-2-methyl-1-propanol, methyldiethanolamine, dimethylethanolamine, diethylethanolamine, triisopropanolamine, ammonia water or triethylamine; The molar ratio of the neutralizing agent to the molar ratio of the chain extender is 0.9 to 1.
1.
8. The method for preparing high solid content waterborne polyurethane by internal-external emulsification according to claim 1, characterized in that: At least one of the following is met: The temperature of the temperature-raising reaction is 60-100°C; The temperature reaction time is 2 to 6 hours; The cooling is to cool to below 30°C; The neutralization reaction time is 10 to 60 minutes; The stirring speed of the external emulsification reaction is 200-800 rpm; The external emulsification reaction time is 0.5 to 2 hours.
9. The waterborne polyurethane prepared by the internal-external emulsification preparation method of high solid content waterborne polyurethane according to any one of claims 1 to 8 is characterized in that: The solid content of the obtained waterborne polyurethane is not less than 48%.
10. Use of the aqueous polyurethane prepared by the internal-external emulsification preparation method of the high-solid content aqueous polyurethane according to any one of claims 1 to 8 or the aqueous polyurethane according to claim 9 in inks, coatings, adhesives or textiles.
Citation Information
Patent Citations
Waterborne polyurethane dispersion as well as preparation method and application thereof
CN117003986A
Cited By
Water-resistant high-solid-content cross-linked waterborne polyurethane as well as preparation method and application thereof
CN121758719A
Degradable polyurethane elastomer, preparation method thereof and mechanical-electric coupling artificial blood vessel
CN122080361A